Modification and sensory evaluation of Turkish delight (lokum); supplemented with different levels of dried date powders - ALRASHEEDI, Amani Alawi; ALI, Asmahan Azhari; HIJAZI, Maha Ahmed (Food Science and Technology, 2023)
Thise current study aimed to investigate the impacts and sensory properties of replacing gelatin in Turkish delight with starch and dried date powder (DDP) for the development of new products. Nine different concentrations of fluid mucilage were used: Sample 1 (90% gelatin + 10% starch); Sample 2 (90% gelatin + 5% starch + 5% DDP); Sample 3 (85% gelatin + 10% starch + 5% DDP); Sample 4 (80% gelatin + 20% starch); Sample 5 (80% gelatin + 10% starch + 10% DDP); Sample 6 (75% gelatin + 20% starch + 5% DDP; 70% gelatin + 30% starch); Sample 7 (70% gelatin + 15% starch + 15% DDP); and Sample 8 (65% gelatin + 30% starch + 5% DDP) in addition to a control sample (Sample 9, 100% gelatin). Consistency, texture, and tenderness of all samples (gel and water activities; aw) were evaluated in terms of taste, aftertaste, and overall acceptability. The sensory panelists’ scores of collected data showed significant differences between all measured parameters for all compared to with the control sample, but the best products were with samples with added (DDP) at low levels. In conclusion, replacing gelatin with starch and (DDP) should be at low levels.